Sustainability development: part 1 - from the cybernetic of cybernetics to the cybernetics of development. (2018) - Yolles, Maurice
This paper is in three parts. The first part explains how von Foerster came to define second order cybernetics through Piaget's child learning model. It inherently relates this to the metasystem-system relationship that underpins Stafford Beer's management cybernetics and its connection to self-processes for the adaptive autonomous system. It also explains how the Foerster's concepts of eigenvalues and eigenbehaviour connect these. Using agency theory, von Foerster's schema is extended to embrace the third order cybernetic complex adaptive systems, leading to the idea of eigendevelopment. Part 2 of this paper posits that, through eigenbehaviours, agency interests arise that are represented generically through amenities. The issue of sustainability development is an important one that requires society to understand the relationship between different independent systems, identified from the literature. In part 3 the different systems and their amenities are explored, and discussion occurs about how the systems, as agencies, may co-evolve in order to lead to sustainability.